2007
DOI: 10.1091/mbc.e07-05-0486
|View full text |Cite
|
Sign up to set email alerts
|

RAB-10 Regulates Glutamate Receptor Recycling in a Cholesterol-dependent Endocytosis Pathway

Abstract: Regulated endocytosis of ␣-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid-type glutamate receptors (AMPARs) is critical for synaptic plasticity. However, the specific combination of clathrin-dependent and -independent mechanisms that mediate AMPAR trafficking in vivo have not been fully characterized. Here, we examine the trafficking of the AMPAR subunit GLR-1 in Caenorhabditis elegans. GLR-1 is localized on synaptic membranes, where it regulates reversals of locomotion in a simple behavioral circuit. Anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
104
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(106 citation statements)
references
References 67 publications
2
104
0
Order By: Relevance
“…Neurotransmitter release at the synapse is modulated by factors that control synaptic growth, synaptic vesicle recycling, and receptor turnover at postsynaptic sites (Sweeney and Davis 2002;Glodowski et al 2007;Kim and Kandler 2010;Fernandes et al 2014). Endolysosomal trafficking modulates the function of these factors and therefore plays an important role in regulating synaptic development and function.…”
Section: Discussionmentioning
confidence: 99%
“…Neurotransmitter release at the synapse is modulated by factors that control synaptic growth, synaptic vesicle recycling, and receptor turnover at postsynaptic sites (Sweeney and Davis 2002;Glodowski et al 2007;Kim and Kandler 2010;Fernandes et al 2014). Endolysosomal trafficking modulates the function of these factors and therefore plays an important role in regulating synaptic development and function.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, during the revision process of this manuscript, a study by Glodowski et al, 2007 showed that ITSN-1 regulates ␣-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid-type glutamate receptors trafficking in interneurons, suggesting that ITSN-1 might regulate neurotransmission acting in the whole neuronal circuit (Glodowski et al, 2007). Together, our study and those of Wang et al and Glodowski et al, 2007 provide an initial picture of what might be a basic function of intersectin, upon which other functions might have been added in the course of evolution in more complex organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the Tre-2/Bub2/ Cdc16 (TBC) domain of AS160 inactivates Rabs 2A, 8A, 10, and 14. In 3T3-L1 adipocytes, knockdown of Rab10 expression prevented the insulin-dependent gain in surface GLUT4 (31), and a recent report assigns to Rab10 a role in the recycling of neuronal cargo internalized via cholesterol-dependent endocytosis (53). GLUT4 internalization through this route is more absolute in adipocytes (54) than in muscle cells (55).…”
Section: Characteristics Of Glut4 Traffic In Muscle Cells-skeletalmentioning
confidence: 95%